A prospective comparative study to evaluate the efficacy of ultrasonography and hysteroscopy and their correlation with the histopathology of endometrium in a case of abnormal uterine bleeding - Kumari, Madhu; Gupta, Alka S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding (AUB) is one of the most common complaints that brings a woman to the gynecologist. Key to successful clinical management of AUB is to identify the cause behind it for which proper evaluation of the case is required. In current scenario of increasing cost awareness and taking risk related to invasive procedure hysteroscopy, a balance has to be achieved between the practices of randomly doing all investigation versus a condition appropriate approach. This study was done to compare efficacy of pelvic ultrasonography & hysteroscopy in cases of AUB and their correlation with the histopathology of endometrium. Methods: In this study 70 women with AUB were selected as they presented in OPD. After evaluation of clinical presentation, general, systemic and local examination, ultrasonography and hysteroscopy were performed on every patient and endometrial curetting were sent for histopathology. Results: We concluded that ultrasonography has a better efficacy to detect uterine cause of AUB and hysteroscopy is better for detecting intracavitary lesions. Conclusions: Ultrasonography has a better efficacy to detect uterine cause of AUB. However a thorough history and detailed clinical examination plays a very important role in narrowing the differential diagnosis of AUB. We have developed an algorithmic approach and guidelines for selective use of hysteroscopy in cases of AUB after evaluating the results.